Diagnostic advances in synovial fluid analysis and radiographic identification for crystalline arthritis. Issue 2 (March 2019) - Zell, Monica; Zhang, Dawen; FitzGerald, John
Abstract : Purpose of review: The present review addresses diagnostic methods for crystalline arthritis including synovial fluid analysis, ultrasound, and dual energy CT scan (DECT). Recent findings: There are new technologies on the horizon to improve the ease, sensitivity, and specificity of synovial fluid analysis. Raman spectroscopy uses the spectral signature that results from a material's unique energy absorption and scatter for crystal identification. Lens-free microscopy directly images synovial fluid aspirate on to a complementary metal-oxide semiconductor chip, providing a high-resolution, wide field of view (∼20 mm 2 ) image. Raman spectroscopy and lens-free microscopy may provide additional benefit over compensated polarized light microscopy synovial fluid analysis by quantifying crystal density in synovial fluid samples. Ultrasound and DECT have good sensitivity and specificity for the identification of monosodium urate (MSU) and calcium pyrophosphate (CPP) crystals. However, both have limitations in patients with recent onset gout and low urate burdens. Summary: New technologies promise improved methods for detection of MSU and CPP crystals. At this time, limitations of these technologies do not replace the need for synovial fluid aspiration for confirmation of crystal detection. None of these technologies address the often concomitant indication to rule out infectious arthritis.